Local community outlook on tourism development in Tioman island - MOHD HANAFIAH, MOHD HAFIZ; Abas, Siti Aisah (CRC Press Taylor & Francis Group, 2013)
The tourism industry has been recognized as the symbol to help the local community especially in changing the economic and atmosphere due to the ability to generate income, employment as well improve the standard of living. The attitudes of the local community can directly affect the development of the tourism industry. Positive attitudes from the local residents help in boosting tourists’ satisfaction levels and contribute to the word-of-mouth promotion among international tourists. In order to ensure the success of the tourism planning, the involvement and the involvement of the local communities in the area is pertinent. This study endeavors on local community attitudes’ toward tourism development in Tioman Island. Local residents with personal benefit and positive perception of tourism development will support for future tourism development. However, the finding also revealed that the local community who perceived negative impact of tourism activities also supports the tourism development in the future due to the reliance on this sector as their main income. The role of perceived tourism impact as the moderator between the relationship between personal benefit from tourism and the future attitudes from tourism development become the contribution of this study